Acute myocardial infarction on the background of coronary artery occlusion with low-symptomatic clinical manifestations and no changes on the electrocardiogram - A. G. Pronin; A. A. Troshina; O. I. Slyusar; A. A. Serov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The article presents a clinical observation of the successful treatment of a patient with acute primary myocardial infarction against the background of occlusion of the anterior descending artery without generally accepted, with these volumes of lesions, clinical and electrocardiographic manifestations.